Pengaruh Fear of Missing Out (FOMO) dan Social Media Marketing terhadap Niat Pembelian pada Produk Healthy - Lissa Rosdiana Noer; Prahardika Prihananto; Aqnis Asokawati; Sri Yayu Ninglasari; Ni Gusti Made Rai (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
The food and beverage industry in Indonesia has stimulated a surge inIndonesian youth's practice of consuming nutritious food, resulting in fiercerivalry among enterprises in the healthy food sector. In order to manage thehighly competitive business environment, organizations have increasinglyresorted to utilizing social media marketing as a means to increase consumerinclination to make purchases. However, the widespread use of social mediahas led to concerns about individuals feeling excluded or perceived asoutdated, a phenomenon commonly known as Fear of Missing Out (FOMO).The objective of this study is to examine the influence of Fear of Missing Out(FOMO) through social media marketing on consumers' inclination to makea purchase. We administered a survey using Google Forms to 120 participantsaged between 18 and 34. We then analyzed the collected data using partialleast squares structural equation modeling (PLS-SEM). The results indicatethat both the fear of missing out (FOMO) and social media marketing have abeneficial impact on the desire to purchase healthy food goods. Utilizing thefear of missing out (FOMO) in social media marketing techniques cansuccessfully enhance consumer attention and stimulate sales in the healthyfood industry.